KEPUASAN KERJA SEBAGAI KUNCI OPTIMALISASI KINERJA PEGAWAI PADA DINAS KEHUTANAN SULAWESI TENGAH - Harries Madiistriyatno; Nahardi Nahardi; Ida Musdafia Ibrahim (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
Job satisfaction is one of the keys to accomplish optimal performance. Therefore, conditioning the organization to create job satisfaction is very important. This study aims to prove that the optimization of employee performance can be achieved especially if the job satisfaction has been realized, using career development, competence, and compensation as indicators. This research method was descriptive-verification with the collection data using survey that sampling uses saturated sampling and analyzed using the Structural Equation Model. The object research was employees of the Regional Forestry Service work units of Central Sulawesi Province. The results proved that the job satisfaction was a very important factor in mediating (full mediating variables) the variables of career development, competence, and compensation in improving employee performance, which is indicated by a positive and significant effect. Furthermore, it was proven that the biggest contribution affecting employee performance was the variable job satisfaction, with career development contributes to the highest influence on job satisfaction, followed by competence, and compensation.   Keywords: Job satisfaction, career development, competence, compensation, and employee’s performance.